Model-based adaptive protection scheme for isolated microgrids - Núñez Mata, Óscar Fernando (2015)
Isolated microgrids have received much attention in recent years due to their ability for electrifying zones typically disconnected from the main grid. Among the most important challenges of isolated microgrids is the design and operation of the protection scheme, in order to recognize system abnormalities and faults.